Consultant tender / Muhammad Ammar Zakir Mohd Zamry - Mohd Zamry, Muhammad Ammar Zakir (Universiti Teknologi MARA, Perak, 2021)
This internship report serves the purpose to record the details of my industrial training which was conducted in MMN Bina Sdn Bhd, which is one of the construction company in Kuantan area. This report will cover the details of my internship in the Development for duration of 5 months which began from 23 August till 7 January, 2021 at MMN Bina Sdn Bhd which is located at Semambu, Kuantan, Pahang.Student who are undertaking the course name Diploma in University Technology MARA (UITM) are compulsory to undergo an industrial training at one of the company for a period of 5 months prior to graduating. Student are allowed to make their own choices to enter any company to do their internship, as long as have building background. This is to ensure students will be getting the exposure to involve in building related works instead of other non- building related works. The objectives of this industrial training are to develop a deeper understanding on the course which they are undertaking and to provide the appropriate work-related trainings to them in the field of civil profession.